Effect of foxtail millet supplementation in comparison to atorvastatin on high-fat diet-induced hyperlipidemia in rats - Praneeth Reddy Onteddu,; Suguna Sajja,; Bhuvaneshwari Gajala,; Shravya Edavaluru,; Chaitanya Kandula, (Asian Journal of Medical Sciences, 2023)
Background: Hyperlipidemia can be defined as an increased concentration of lipids in the blood. Foxtail millet (FTM) is a nutrient-rich cereal containing several phytochemicals which have possible lipid-lowering and glucose-lowering abilities. Atorvastatin is an HMG Co-A Reductase Inhibitor commonly prescribed for Hyperlipidemia. Aims and Objectives: The aim of this study was to compare the hypolipidemic effect of FTM with that of Atorvastatin in Sprague–Dawley rats. Materials and Methods: Twelve 12 male Sprague–Dawley rats were segregated into Group-A and Group-B with six (6) rats in each group. The rats in both groups were fed high-fat diet for 21 days and for the next 21 days the 6 rats in Group-A were fed FTM in the form of pellets, the 6 rats in Group-B were administered Atorvastatin in a dose of 5 mg/kg. The body weight (BW) and lipid profiles of the rats were measured at three stages-day 0, day 21, and day 42. Results: FTM showed an 18.1% rise in high-density lipoprotein (HDL-C). It showed a fall in BW, total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL-C), and very LDL (VLDL-C) which were 15.5%, 14.0%, 12.8%, 18.3%, and 16.0%, respectively. With Atorvastatin the rise in HDL-C was 13.4%. The fall in BW, TC, TG, LDL-C, and VLDL-C was 30.2%, 30.5%, 24.9%, 27.5%, and 34.4%, respectively. Conclusion: The present study results showed that FTM had a noticeable positive effect on the lipid profile and BW in Dyslipidemia in comparison to Atorvastatin.